Análisis jurídico sobre la eficacia y recurso de apelación del Habeas Corpus - Vicuña-Zambrano, Victor Manuel; Pupo-Kairuz, Alba Rosa; Paucar-Paucar, Cesar Elias (IUSTITIA SOCIALIS, 2020)
The investigation focused on conducting a legal analysis on the effectiveness and appeal of habeas corpus, based on an inadequate performance of judges in the Criminal Judicial Unit of the Babahoyo Canton, Ecuador. Methodologically, it was focused on the critical legal analysis of habeas corpus as a jurisdictional guarantee in judicial practice, through the analytical-synthetic method. It was evidenced that the guarantee that allows the exercise of the right to freedom of human beings in Ecuador is being violated, which constitutes a serious violation of the presuppositions that are established as a result of the establishment of a rule of law, therefore Therefore, said violation will be obvious to those who have to resolve a request of this nature.